Selena: A Screenplay Exploring Adult Women’s Body Image Issue - Nadya Natasha; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2023)
Body image dissatisfaction is a heavy issue that a lot of women face, yet it lacks perspectives in the eyes of the media. Instead, the issues are more focused on younger, more adolescent girls’ point of view. This lack of depth contributes to a shallower understanding of body image issues since women from many other walks of lives also experience the same thing. This mission is what the creative work strives for. Using the Self-Discrepancy theory, it explores how body image issues appear in an adult woman’s life, how it affects it, as well as how she learns to overcome the problem. The film is emotional with a dash of magic in it, so it falls under the drama and low fantasy genre.